Cognitive counseling an educational video - Holden, Jan; Gradding, Samuel T.; Microtraining Associates; Association for Counselor Education and Supervision ([Framington, Mass.] : Distributed by Microtraining Associates, 1993)
Features clear and specific examples of cognitive strategies for counseling clients representing the lifespan: adolescent, middle adult, and older adult. Jan Holden demonstrates her'10 steps of the cognitive counseling routine.' Her clear, live interviews show strategies such as evaluating distorted vs. viable thinking through becoming the objective observer, examining the evidence, triple column, and cost-benefit analysis; thought stopping; and cognitive and behavioral rehearsal. Samual Gladding helps explain and debrief what occurs in the sessions
Title from title screen
Narrator: Samuel T. Gladding
Counselor: Janice Miner Holden
Clients: Brandi Buckner, Byron Medler, Billy Cleavelin
Keywords: Cognitive therapy; Counseling; Psychotherapy